1997
DOI: 10.1002/(sici)1096-9861(19970901)385:3<456::aid-cne9>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate receptor subunit 2-selective antibody shows a differential distribution of calcium-impermeable AMPA receptors among populations of neurons

Abstract: Alpha-Amino-3-hydroxy-5-methyl-4-isoxazolepropionate (AMPA) receptors are the major excitatory neurotransmitter receptors of the central nervous system. AMPA receptor complexes that contain the AMPA-type glutamate receptor subunit 2 (GluR2) are responsible for the low calcium permeability typical of most AMPA receptors, and the absence of GluR2 may be a key factor in neurotoxicity. A polyclonal antibody was produced to a 16 amino acid peptide near the C-terminus of GluR2 and was affinity-purified in a three-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
114
0
5

Year Published

1998
1998
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(150 citation statements)
references
References 62 publications
(89 reference statements)
31
114
0
5
Order By: Relevance
“…Whereas a minority of GABAergic interneurons express GluR-B at levels comparable with pyramidal cells (34), in most GABAergic interneurons this subunit is expressed at significantly lower levels. This expression pattern has been documented by in situ hybridization (35)(36)(37) and immunocytochemistry (34,(38)(39)(40)(41). Low GluR-B expression in GABAergic cells affects a number of AMPA receptor properties, including Ca 2ϩ permeability (31,32,42,43), block by polyamines (44), and single-channel conductance (22), and is the molecular basis for certain novel forms of plasticity (44)(45)(46).…”
Section: Discussionmentioning
confidence: 97%
“…Whereas a minority of GABAergic interneurons express GluR-B at levels comparable with pyramidal cells (34), in most GABAergic interneurons this subunit is expressed at significantly lower levels. This expression pattern has been documented by in situ hybridization (35)(36)(37) and immunocytochemistry (34,(38)(39)(40)(41). Low GluR-B expression in GABAergic cells affects a number of AMPA receptor properties, including Ca 2ϩ permeability (31,32,42,43), block by polyamines (44), and single-channel conductance (22), and is the molecular basis for certain novel forms of plasticity (44)(45)(46).…”
Section: Discussionmentioning
confidence: 97%
“…This antibody was a kind gift of Dr. Jean-Marc Fritschy (Institute of Pharmacology, University of Zurich, Zurich, Switzerland). All of these antibodies have been thoroughly characterized and widely used for immunocytochemical localization of glutamate and GABA receptors with light and electron microscopic immunocytochemistry (Petralia and Wenthold, 1992;Petralia et al, 1994Petralia et al, , 1997Fritschy and Mohler, 1995;Nusser and Somogyi, 1997;Takumi et al, 1999b).…”
Section: Methodsmentioning
confidence: 99%
“…Age-related decline of neuronal densities in these regions did not exceed 2-3% (Table 2). Morphological analysis indicated that neurodegeneration occurring in the brain and spinal cord of GluR-B(N) mice follows the GluR-B expression pattern (16) and is preferentially accelerated in the ventral horns of the spinal cord, the basolateral amygdaloid nucleus, and in the ventromedial hypothalamic nucleus. The ventral horns in the spinal cord are essential in the regulation of muscle tone and the execution of movements (17), the basolateral amygdaloid nucleus plays a key role in the perception of fear (18), and the ventromedial hypothalamic nucleus is involved in the regulation of food intake (satiety center) (19).…”
Section: Density Of Neurons In the Brains Of Wt And Glur-b(n) Micementioning
confidence: 99%